Functional and radiological outcome of both bone fracture forearm in children managed with titanium elastic nailing system - Butt, Muhammad Farooq; Ayaz, Saqib; Malik, Irfan; Anwar Ahmed, M.; Lone, Zubair Ahmad (International Journal of Research in Medical Sciences, 2025)
Background: Forearm diaphyseal fracture is one of the three common upper limb fractures in the pediatric population. With many known methods of treatment available, the authors present their experience of managing these injuries by titanium elastic nailing system. Methods: The present study was a prospective study of 3 years duration which included 50 patients. All patients underwent elastic nailing of both radius and ulna in the same sitting. Analysis of pre-operative and post-operative radiographs of forearm, taken in two orthogonal views, was done. Final functional outcome was graded clinically by using criteria laid down by Price et al. Results: Good to excellent results were achieved after elastic nailing of forearm fractures in all the children. In this study, bony union was achieved in a mean time of 8.36 weeks, range being 6 to 14 weeks. No case of non-union was observed in the present study. Pin tract infection and skin irritation were the most common complication observed. Conclusions: Elastic stable intramedullary nailing is a safe and reliable method for internal fixation, giving predictably good functional results in paediatric both bone forearm fractures.